Understanding factors influencing elderly diabetic patients' continuance intention to use digital health wearables: Extending the Technology Acceptance Model (TAM) - Ashfaq Ahmad; Tareq Rasul; Anish Yousaf; Umer Zaman (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Elderly diabetic patients in developed countries have been widely using digital health wearables for many years to manage their diabetes-related health data accurately. To encourage the increased adoption of digital health wearables among elderly diabetic patients in a developing country, Bangladesh, this study investigated the factors that influenced the existing elderly users' continuance intention to use this technology. The Technology Acceptance Model (TAM) has been used here as a theoretical basis. A model using structural equation modelling was developed for the elderly diabetic patients' continuance intention to use digital health wearables. Survey-based data were collected in Bangladesh from 223 diabetic patients aged sixty years and older. This study found that all six constructs, namely, perceived usefulness (Ø = 0.183), perceived ease of use (Ø = 0.165), perceived irreplaceability (Ø = 0.138), perceived credibility (Ø = 0.165), compatibility (Ø = 0.285) and social influence (Ø = 0.226) had a positive influence on elderly diabetic patients' continuance intention to use digital health wearables. Along with the theoretical contributions, the findings of this study can be used by developers of digital health wearables, manufacturers, marketers and health practitioners in developing better strategies to increase the elderly diabetic patients' continuance intention to use this technology.
Keywords: 650; digital health wearables; healthcare technology; diabetes; technology acceptance model (TAM)